THE USE OF GENETALIA CLEANING LIQUID AGAINST WHITENESS IN ADOLESCENT - Pramesti Anggita Putri; Yunik Windarti (Siklus : Journal Research Midwifery Politeknik Tegal, 2022)
Vaginal discharge often occurs in many women. One of the influencing factors is personal hygiene habits. One of these personal hygiene behaviors is how to clean the genital organs that are less precise. The purpose of the study was to analyze the effect of using genital cleansing fluid on vaginal discharge in adolescents. Non-experimental research design: cross-sectional analytic, sample size 67 with simple random sampling technique, questionnaire instrument and tested with Chi-Square. The results of the study, most (62.7%) adolescents used genital cleaning fluid and most (64.2%) experienced pathological vaginal discharge. Adolescents who used genital cleansing fluid almost entirely (79%) experienced pathological vaginal discharge. The value of = 0.001 = o.o5 means that there is a significant effect. The risk of the occurrence of vaginal discharge will be even greater if you use genital cleaning fluid. It is expected that teenagers clean the genital organs properly and precisely without using genital cleaning fluids